Ulcers and nodular lesions linearly disposed - Gil, María Eugenia; Torre, Ana Clara; Bollea Garlatti, Agustín Luis; Stefanini, Lucas; Kowalczuk, Alicia María; Galimberti, Ricardo Luis (Revista del Hospital Italiano de Buenos Aires, 2014)
Nodular lymphangitis, is due to a germ inoculation through the skin and is characterized by the involvement of this, lymphatic vessels and lymph nodes in the territory committed. It can be produced by several fungi, bacteria, viruses and parasites, being the most frequent Sporothrix schenckii, Nocardia brasiliensis, Mycobacteria marinum and Leishmania brasiliensis. We report a 40-year-old man with an advanced cavum malignant tumor under chemotherapy that was attended by nodular lymphangitis on his left upper limb. Skin cultures and histological study of skin lesions allowed us to diagnose Sporotrix schenkii infection, which resolved after treatment with itraconazole 200 mg/day orally